Development of Culinary Products in Gamplong Tourism Village Through Local Food Innovation and Marketing: Pengembangan Produk Kuliner Desa Wisata Gamplong Melalui Inovasi Pangan Lokal dan Pemasaran - Nuvriasari, Audita; Harsoyo, Titik Desi; Rozi, Anief Fauzan; Fitri, Ichlasia Ainul (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Gamplong Tourism Village has local food resources in the form of garden produce that have not been optimally utilized due to the limited knowledge and skills of the local community in developing local food processing. Community service is aimed at developing culinary local products through innovations in food processing that have economic value and appropriate marketing. The activity method is training and counseling by involving active participation from partners. The results of the activity show an increase in insight and skills of partners in innovating local food processing so that the product results are more varied. In addition, partners increasingly understand marketing techniques so that local culinary products are more in demand by tourists. This program also developed labeling, packaging and product catalog designs. Product and marketing innovation is one of the important keys so that culinary product can become one of the sources of attraction for Gamplong Tourism Village.